IMPLEMENTASI SSL ( SECURE SOCKET LAYER ) UNTUK MELINDUNGI TRANSAKSI ONLINE - Rakhmadi Rahman; Nurislamiyah Nurislamiyah (CV. Denasya Smart Publisher, 2024)
The security of online transactions is crucial in today's digital era. This study aims to examine the impact of the implementation of Secure Socket Layer (SSL) on the security of online transaction websites. Prior to the implementation of SSL, websites were often vulnerable to attacks such as data theft and man-in-the-middle attacks due to the use of the insecure HTTP protocol. By implementing SSL, data is encrypted between the server and the user, and digital certificates are used to authenticate the identity of the website, increasing protection against sensitive data such as credit card information and personal data. The research method used is action research, with a recurring cycle of planning, action, observation, and reflection. The results of the study show that after the implementation of SSL, there is a significant increase in the security of online transactions. The transmitted data is effectively encrypted, reducing the risk of man-in-the-middle attacks and phishing. Strong server authentication also builds user trust, which is reflected in the increase in online transaction activity. The conclusion of this study is that SSL is an essential step to improve security and trust in online transactions, and provides recommendations for further development in the application of this technology.